2021
DOI: 10.1101/2021.02.04.429751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targetedin situcross-linking mass spectrometry and integrative modeling reveal the architectures of Nsp1, Nsp2, and Nucleocapsid proteins from SARS-CoV-2

Abstract: Atomic structures of several proteins from the coronavirus family are still partial or unavailable. A possible reason for this gap is the instability of these proteins outside of the cellular context, thereby prompting the use of in-cell approaches. In situ cross-linking and mass spectrometry (in situ CLMS) can provide information on the structures of such proteins as they occur in the intact cell. Here, we applied targeted in situ CLMS to structurally probe Nsp1, Nsp2, and Nucleocapsid (N) proteins from SARS-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…At the structural level, NSP2 has a complex multi-domain topology including an N-terminal domain with a highly conserved zinc binding site, and a C-terminal region rich in b-strands. With the exception of the zinc binding site, NSP2 displays a rapidly evolving surface with the presence of natural variations that could impact host-virus interactions (Ma et al, 2021;Mompean et al, 2021;Gupta et al, 2021;Slavin et al, 2021). Among its host interactors, SARS-CoV-2 NSP2 interacts with the 4EHP-GIGYF2 complex, a key machinery in translational silencing and mRNA decay (Davies et al, 2020;Cornillez-Ty et al, 2009;Gordon et al, 2020aGordon et al, , 2020b.…”
Section: Introductionmentioning
confidence: 99%
“…At the structural level, NSP2 has a complex multi-domain topology including an N-terminal domain with a highly conserved zinc binding site, and a C-terminal region rich in b-strands. With the exception of the zinc binding site, NSP2 displays a rapidly evolving surface with the presence of natural variations that could impact host-virus interactions (Ma et al, 2021;Mompean et al, 2021;Gupta et al, 2021;Slavin et al, 2021). Among its host interactors, SARS-CoV-2 NSP2 interacts with the 4EHP-GIGYF2 complex, a key machinery in translational silencing and mRNA decay (Davies et al, 2020;Cornillez-Ty et al, 2009;Gordon et al, 2020aGordon et al, , 2020b.…”
Section: Introductionmentioning
confidence: 99%
“…A study focusing on three proteins of the SARS-CoV-2 virus (Nsp1, Nsp2 and nucleocapsid) expressed strep tagged versions of the viral proteins in HEK293 cells prior to cross-linking the cells with DSS . The cells were lysed and the viral proteins were purified via the strep tag prior to XL-MS analysis.…”
Section: Ms Structural Biology In Cellsmentioning
confidence: 99%
“…The cells were lysed and the viral proteins were purified via the strep tag prior to XL-MS analysis. Identified cross-linked residues served as distance restraints for integrative modeling and domain assembly of Nsp2, olgimerization and domain assembly of nucleocapsid, and complex assembly between the viral protein Nsp1 and the host ribosomal protein RS3 . Importantly the authors found that the in situ cross-linking results were not fully replicated by in vitro experiments indicating protein states that are unique to the cellular environment …”
Section: Ms Structural Biology In Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-terminal domain could be located in the cryo-EM maps but at too low a resolution to allow model building, presumably due to flexibility with respect to the 40S. The cryo-EM derived location of the Nsp1 N-terminal domain in the ribosomal complex is further supported by in situ cross-linking mass spectrometry identifying multiple crosslinks between Nsp1 and ribosomal protein S3 (18,20).…”
Section: )mentioning
confidence: 99%